Copper‐Coated Liquid‐Crystalline Elastomer via Bioinspired Polydopamine Adhesion and Electroless Deposition. Issue 23 (26th September 2016) - Frick, Carl P.; Merkel, Daniel R.; Laursen, Christopher M.; Brinckmann, Stephan A.; Yakacki, Christopher M.
Abstract : This study explores the functionalization of main‐chain nematic elastomers with a conductive metallic surface layer using a polydopamine binder. Using a two‐stage thiol‐acrylate reaction, a programmed monodomain is achieved for thermoreversible actuation. A copper layer (≈155 nm) is deposited onto polymer samples using electroless deposition while the samples are in their elongated nematic state. Samples undergo 42% contraction when heated above the isotropic transition temperature. During the thermal cycle, buckling of the copper layer is seen in the direction perpendicular to contraction; however, transverse cracking occurs due to the large Poisson effect experienced during actuation. As a result, the electrical conductivity of the layer reduced quickly as a function of thermal cycling. However, samples do not show signs of delamination after 25 thermal cycles. These results demonstrate the ability to explore multifunctional liquid‐crystalline composites using relatively facile synthesis, adhesion, and deposition techniques. Abstract : A main‐chain nematic liquid‐crystalline elastomer (LCE) is functionalized with a conductive copper surface via polydopamine adhesion and electroless deposition. The programmed monodomain LCE exhibits thermomechanical contraction up to 42% causing the copper film to buckle reversibly. The film does not delaminate through 25 thermal cycles. These results demonstrate a facile technique to metallize shape‐switching polymers.